High speed railway operations expert training development in Indonesia - Riyanta, Wawan; Jannah, Anggra Iftitah Miftakhul (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
KCIC Phase I Training Program will accommodate 500 Participants from the total HR needs of PT KCIC from 1,452 people. The focus is on increasing competence on the Operation System, Passenger Service, and Maintenance divided into 21 Training Posts, most of the participants came from Fresh Graduates who entered the Entry Level. Required Competence Levels ability to apply knowledge and skill High Speed Railway Technology. technical executive level for High Speed Railway operation and maintenance for Electric Multiple Unit (EMU) KCIC400AF Type from China. Gaps participant competence between existing competence levels and required competence levels calculate 100%, thus the training program will be carried out as a whole in accordance with the training curriculum of the HSRCC. The training program consists of 4 parts consisting of (1) Indonesian regulation, instructors from Indonesian Railway Polytechnic; (2) Professional Knowledge, instructor from Tianjin Railway Technical and Vocational College and Southwest Jiaotong University; (3) Safety & regulation, instructor from China Railway – Beijing; and (4) Practical skills instructor from China Railway – Beijing. The delivery method uses the online class method which will be accompanied by interpreters and assistant lecturers in each class. With the language interpretation stage, a multiplier coefficient of 2.5 is obtained from normal lesson hours in the HSRCC curriculum if it is implemented in Indonesian participants. The duration of the training implementation about 1 – 8.5 Month. The next competency requirement is High Speed Railway trainer from Indonesia. With the stipulation, which was conveyed by the HSRCC, that participants who have taken the training phase I and received an evaluation score of training and competency certification above the average of other participants, are able to take part in the Training of Trainers for High Speed Railway and pass the Competency Test of Trainer Candidates.